Woman and work at margin - Delgado Ruiz, José (FEMERIS: Revista Multidisciplinar de Estudios de Género, 2020)
Abstract. Moving through the labyrinths that hides the discrimination of women requires a courageous and determined attitude. Especially because in that territory the positions must be marked, without half measures. Observing from indifference or distance does not produce a break or risk some. But the message takes on another meaning and comes with other sounds when that situation has been experienced in the first person; then the words are perceived as darts that stir the conscience. This is the case in the present story whose main character is a survivor who, in the framework of a university congress on discrimination by gender and work, receives all kinds of content, technical and elaborated, on equal opportunities between women and men. And spontaneously submitting all that information to the filters of his criticism and experience reaches very personal conclusions.
Keywords: discrimination; women; gender; work; decency